2007
DOI: 10.1200/jco.2006.08.9599
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Induced Long-Term Hearing Impairment Is Associated With Specific Glutathione S-Transferase Genotypes in Testicular Cancer Survivors

Abstract: The presence of both alleles of 105Val-GSTP1 offered protection against cisplatin-induced hearing impairment. Two genotype patterns with good and poor protection against cisplatin-induced ototoxicity were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(124 citation statements)
references
References 35 publications
(6 reference statements)
3
116
3
1
Order By: Relevance
“…Our findings support the hypothesis that increased cisplatin sensitivity may in part be due to impaired GSTP1 zenzyme function. Previous studies found the homozygosity GSTP1 105 Val was even more protective against cisplatin-related toxicity in testicular and ovarian cancer (Choueiri et al, 2007;Oldenburg et al, 2007). In our study, we did not observe such association, we found the patients with Val/Val genotype had a higher risk of death from osteosarcoma (HR=2.35, 95% CI=1.13-4.85).…”
Section: Discussioncontrasting
confidence: 82%
“…Our findings support the hypothesis that increased cisplatin sensitivity may in part be due to impaired GSTP1 zenzyme function. Previous studies found the homozygosity GSTP1 105 Val was even more protective against cisplatin-related toxicity in testicular and ovarian cancer (Choueiri et al, 2007;Oldenburg et al, 2007). In our study, we did not observe such association, we found the patients with Val/Val genotype had a higher risk of death from osteosarcoma (HR=2.35, 95% CI=1.13-4.85).…”
Section: Discussioncontrasting
confidence: 82%
“…Overall, evidence regarding an effect of GSTP1 rs1695 on ototoxicity is thus inconsistent (Table S4) (+ evidence). Finally, associations with cisplatin-induced ototoxicity have also been reported for GSTM1 (Table S5) 36,37 and GSTT1 (Table S6) 39 . However, numerous other studies have not replicated these associations 15,[35][36][37][38]41,42 (+ evidence).…”
Section: Gluthathione S-transferases (Gsts)mentioning
confidence: 99%
“…_ENREF_50However, a second study investigating GST polymorphisms in ovarian cancer patients could not replicate this association 38 (+ evidence). In a study by Oldenburg et al, GSTP1 rs1965 was significantly associated with cisplatininduced ototoxicity in adult testicular cancer survivors (Table S4) 36 . However, this association did not achieve statistical significance in an extended patient cohort 37 .…”
Section: Gluthathione S-transferases (Gsts)mentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione is believed to be involved in the cellular detoxification of Pt compounds. There is an indication that the polymorphisms of genes encoding glutathione transferase are relevant for clinical response and development of toxicity (Stoehlmacher et al, 2002;Lecomte et al, 2006;Oldenburg et al, 2007). Thus, the detection and identification of reaction products of Pt-containing drugs with thiol compounds is important in studies of toxicities.…”
Section: Speciation Of Reaction Products Of Metal-based Anticancer Comentioning
confidence: 99%